GAME-BASED LEARNING AS AN INNOVATIVE STRATEGY IN INDONESIAN LANGUAGE LEARNING - Ida Ayu Made Wedasuwari; Ida Bagus Nyoman Mantra; I Gusti Agung Ayu Dwi (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the implementation of Game-Based Learning (GBL) as an innovative strategy in Indonesian language learning through a theoretical review. The method employed is a literature review examining various articles, journals, and theses related to the implementation of GBL. Data were collected through a systematic literature search in academic databases such as Google Scholar, SINTA, GARUDA, and university repositories. The findings indicate that GBL enhances students’ motivation, engagement, and learning outcomes. Media such as Kahoot!, Wordwall, Genially, Classcraft, and project-based games effectively support reading, writing, speaking, and text comprehension skills. GBL also promotes the development of 21st-century skills (4C), namely critical thinking, creativity, collaboration, and communication. However, its implementation faces challenges, including limited teachers’ digital literacy, technological readiness, potential distractions, and unequal access to devices. Overall, GBL has strong potential to improve the quality of Indonesian language learning when systematically designed and supported by adequate teacher competence.